Diabetic Neuropathies - Izenberg, Aaron; Perkins, Bruce A.; Bril, Vera (Seminars in Neurology, 2015)
Diabetes mellitus is a common condition and diabetics are prone to develop a spectrum of neuropathic complications ranging from symmetric and diffuse to asymmetric and focal neuropathies that may be associated with significant morbidity. Diabetic sensorimotor polyneuropathy is the most common of these complications, occurring in patients with type 1 and 2 diabetes mellitus, as well as in those with prediabetes and glucose intolerance. In this review, the authors discuss the wide variety of neuropathies that can present in the context of diabetes, including the clinical manifestations, diagnostic features, and approach to management.
Keywords: diabetes; diabetic neuropathy; neuropathy; polyneuropathy